2008
DOI: 10.1164/rccm.200802-321oc
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Regional Cerebral Oxygenation in Children with Sleep-disordered Breathing

Abstract: Rationale: An association between neurocognitive deficits and pediatric sleep-disordered breathing has been suggested; however, weak correlations between disease severity and functional outcomes underscore the lack of knowledge regarding factors modulating cognitive morbidity of sleep-disordered breathing. Objectives: To identify the parameters affected by sleep-disordered breathing that modulate cerebral oxygenation, an important determinant of cognition. A further objective was to use these parameters with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 35 publications
2
25
0
1
Order By: Relevance
“…In addition, an association between increased arousal index and SDB severity was observed among our tested children, with results that were similar to previous studies [35,36]. The differences in polysomnographic parameters observed in the current study were similar to other children research including sleep efficiency and sleep stages, although AHI classification was different [35,36].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, an association between increased arousal index and SDB severity was observed among our tested children, with results that were similar to previous studies [35,36]. The differences in polysomnographic parameters observed in the current study were similar to other children research including sleep efficiency and sleep stages, although AHI classification was different [35,36].…”
Section: Discussionsupporting
confidence: 91%
“…The differences in polysomnographic parameters observed in the current study were similar to other children research including sleep efficiency and sleep stages, although AHI classification was different [35,36]. We also observed an oxygen deficit in children with severe SDB, AHI>15 group.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Khadra et al 62 reported that male gender, arousal index, and amount of non-rapid eye movement sleep were associated with diminished cerebral oxygenation, whereas increasing mean arterial pressure, age, oxygen saturation (SpO 2 ), and amount of rapid eye movement sleep were associated with augmented cerebral oxygenation (level III). Hogan et al 48 found a decrease in middle cerebral artery velocity postoperatively in patients treated for OSAS, whereas control subjects showed a slight increase over time (level IV).…”
Section: Cardiovascular Effects Of Osasmentioning
confidence: 99%
“…50,51 In the mature brain, CBF usually overshoots the metabolic demands of AS resulting in an increase in oxygenated Hb relative to deoxygenated Hb and therefore increased cerebral TOI. 52 At 2 to 4 weeks CA, the CBF-metabolism coupling response appears to be relatively immature with inadequate increases in CBF 22 during AS resulting in increased oxygen extraction, increased deoxygenated Hb, and decreased cerebral TOI. The reversal of this observation at 5 to 6 months CA suggests that maturation of CBF-metabolism coupling is occurring during this period.…”
Section: Effects Of Sleep Statementioning
confidence: 99%